PENGARUH BIAYA LINGKUNGAN DAN KINERJA LINGKUNGAN TERHADAP PROFITABILITAS PERUSAHAAN PEMENANG KATEGORI ISRA TAHUN 2018 - Amanda Oktariyani (Universitas Tridinanti, 2020)
ABSTRACT This study aims to determine the influence of environmental cost, firm size proxied by total asset and environmental performance proxied by environmental certification of ISO 14001 on the operating income of the winners in Indonesia Sustainability reporting Awards (ISRA) 2018. The population of this study is all the winners of Indonesia Sustainability Reporting Awards in 2018 and they have reported The Sustainability Report for three years from 2016 until 2018. The result show that environmental cost and environmental performance have no influence on the operating income, while firm size has a significant influence on the operating income. Simultanously, environmentalcost, firm size and environmental performance have a significant influence on the operating income.Keywords :Environmental Cost, Firm Size, Environmental Performance, Operating Income, Indonesia Sustainability Reporting Awards, Sustainability Report, Panel Data Regression